God of liberty : a religious history of the American Revolution - Kidd, Thomas S. (New York : Basic Books, 2010)
In God of Liberty, historian Thomas S. Kidd argues that the improbable partnership of evangelicals and Deists saw America through the Revolutionary War, the ratification of the Constitution, and the election of Thomas Jefferson in 1800. --from publisher description
"Rebellion to tyrants is obedience to God" : religion and the American Revolution -- "No king but Jesus" : the Great Awakening and the first American Revolution -- "The sacred property of every man" : radical Christians and the struggle for religious liberty in America -- "The Pope, the Devil, and all their emissaries" : the Bishop Controversy and Quebec Act -- "Victory over the Beast" : the evangelical roots of revolution -- "A Christian Sparta" : virtue and the American Revolution" -- "A time of war" : chaplains, virtue, and Providence -- "God has made of one blood all nations of men" : equality by creation -- "The bands of wickedness" : slavery and the American Revolution -- "One God, three gods, no god, or twenty gods" : disestablishing America's state churches -- "Saving this land" : revivals and the era of American Revolution - -"If men were angels: : virtue, freedom, and the Constitution -- "Jefferson-- and no God!" : the Election of 1800 and the triumph of religious liberty -- "Freedom sees religion as its companion" : faith and American civil society.
Includes bibliographical references and index.
Keywords: United States -- Church history -- 18th century; United States -- History -- Revolution, 1775-1783 -- Religious aspects; Christianity and politics -- United States -- History -- 18th century